Heart rate recovery in patients with inflammatory bowel disease in clinical remission (Annals of Medical Research, 2023)
Aim: The purpose of this report was to assess Heart Rate Recovery (HRR) which is known to be a predictor of cardiovascular diseases in patients diagnosed with Inflammatory Bowel Disease (IBD).Materials and Methods: Fifty-two patients (41 patients with Ulcerative Colitis (UC) and 11 patients with Crohn's Disease (CD)) in remission and 50 healthy volunteers were enrolled in the study. All participants was performed treadmill exercise testing. HRR was expressed as the decrease in the heart rate from peak exercise value to 1 min and 2 min after the exercise. The HRR index was calculated for the first (HRR1) and the second (HRR2) minutes of the recovery phase.Results: The maximal and baseline heart rate during exercise stress test were the same in control groups ,UC and CD (156.6±13.3 vs. 153.8±12.7 vs 152.7±13.6, p=0.432; 93.18±16.37, 94.05±14.8 vs. 86.5±13.9, p=0.313, respectively). Also, there was no difference between the groups in means of the first and the second minute HRR indices (HRR1: 30.7±11.8, 34.5±8.8, 33.9±13.5, p=0.403; HRR2: 51.4±15.4, 54.1±14.6, 55.1±16.9, p=0.807).Conclusion: Many systemic inflammatory diseases are thought to be related to an increased risk of cardiovascular diseases. This association has not been well determined in patients with IBD. We found that the HRR index was not different between the CD and UC patients in remission in this report. Further studies may be needed in this way, and all IBD patients should be suspected of the presence of cardiovascular risk factors to reduce mortality and morbidity.